Lag Schedules and Functional Communication Training: Persistence of Mands and Relapse of Problem Behavior. Issue 3 (May 2018) - Falcomata, Terry S.; Muething, Colin S.; Silbaugh, Bryant C.; Adami, Summer; Hoffman, Katherine; Shpall, Cayenne; Ringdahl, Joel E.
We evaluated the effects of lag schedules of reinforcement and functional communication training (FCT) on mand variability and problem behavior in two children with autism spectrum disorder. Specifically, we implemented FCT with increasing lag schedules and compared its effects on problem behavior with baseline conditions. The results showed that both participants exhibited low rates of problem behavior during treatment relative to baseline during and following schedule thinning (up to a Lag 5 schedule arrangement). Variable and total mands remained high during schedule thinning. With one participant, variable manding persisted when the value of the lag schedule was reduced to zero. The current results are discussed in terms of implications for training multiple mand topographies during FCT for the potential prevention and/or mitigation of clinical relapse during challenges to treatment.